Carbon Emission and Optimization of Energy for Sustainable Development: Rethinking the Possibility - Idowu, Samuel Sunday; Mustapa, Siti Indati; Joshua, Segun (Frontiers in Energy Research, 2021)
The adverse effects of climatic change and environmental degradation associated with the fossil energy sources from crude oil, coal, and gas have been used as a sad commentary by some transnational organizations and multilateral concern. Thus, such campaigns, actions, and concerted efforts are geared towards making them redundant while canvassing for renewable energy sources as perfect alternatives. Although gas is characterized by lower carbon emission, it is somehow not considered as a source capable of being improved upon for a sustainable energy source. Hence, this research is undertaken to project the viability of gas energy with a minimum deleterious impact on nature and humanity. With secondary data sources, the study employed a descriptive research method and employed dynamic capabilities theory as a framework. It was discovered through the study that state politicking that surrounds the current moves to jettison the fossil energy, and the multilateral concern also backs the ploy towards its abandonment, resulting in the development of cold feet towards renewing interests in engaging science, technology, and innovation to further decarbonize the gas energy. The authors suggest, among others, the need for a deliberate engagement of a cutting-edge research and innovative technology through collaborations among countries and international organizations such as OPEC and oil firms. If this is done, it will enhance its relevance even without compromising the minimum biosafety and environmental standards.